2015
DOI: 10.1080/01635581.2015.1073757
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prediagnostic Serum 25-Hydroxyvitamin D Concentration and Glioma

Abstract: There are no previous studies of the association between prediagnostic serum vitamin D concentration and glioma. Vitamin D has immunosuppressive properties; as does glioma. It was, therefore, our hypothesis that elevated vitamin D concentration would increase glioma risk. We conducted a nested case–control study using specimens from the Janus Serum Bank cohort in Norway. Blood donors who were subsequently diagnosed with glioma (n = 592), between 1974 and 2007, were matched to donors without glioma (n = 1112) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…While vitamin D and its metabolites have been shown to induce death of glioblastoma cells 20 22 , only one epidemiological study has investigated the relationship between pre-diagnostic levels of 25(OH)D and glioma risk 23 . Researchers found that higher levels of 25(OH)D were protective against high-grade glioma in men over the age of 56 (OR = 0.59), although the reverse trend was shown in men under the age of 56, albeit at a borderline-significant level 23 . Excluding the possibility of post hoc data mining, such paradoxical findings would support distinct aetiologies between the GBM and non-GBM subtypes, as has been suggested previously 9 .…”
Section: Discussionmentioning
confidence: 99%
“…While vitamin D and its metabolites have been shown to induce death of glioblastoma cells 20 22 , only one epidemiological study has investigated the relationship between pre-diagnostic levels of 25(OH)D and glioma risk 23 . Researchers found that higher levels of 25(OH)D were protective against high-grade glioma in men over the age of 56 (OR = 0.59), although the reverse trend was shown in men under the age of 56, albeit at a borderline-significant level 23 . Excluding the possibility of post hoc data mining, such paradoxical findings would support distinct aetiologies between the GBM and non-GBM subtypes, as has been suggested previously 9 .…”
Section: Discussionmentioning
confidence: 99%
“…glioma risk in men >56 at diagnosis (Zigmont et al, 2015). A Mendelian randomization study showed that there is an inverse relationship between 25(OH)D levels and glioblastoma risk using the inverse-variance weighted method (Takahashi et al, 2018).…”
mentioning
confidence: 99%
“…Zigmont et al in 2015 published the fi rst study in which they evaluate a potential association between pre-diagnostic serum vitamin D and glioma risk. They found that men older than 56 years with higher levels of serum 25(OH)D had a reduced risk of glioma (60).…”
Section: Discussionmentioning
confidence: 99%